The boy who held back the sea - Hort, Lenny; Locker, Thomas 1937- .; Dodge, Mary Mapes 1830-1905. (New York Puffin Pied Piper, 1991)
By blocking a leaking hole in the dike, a young boy saves his town from destruction.
Adaptation of: Hans Brinker, or The silver skates / Mary Mapes Dodge.
Keywords: Netherlands -- Fiction